The Connection Between Hackers and Their Affinity Towards Healthcare - McBride, Maurice L (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Cybercriminals target the healthcare sector because patient data can be traded illegally. These include ransomware attacks and medical record theft. This article analyzes the internal factors that make healthcare firms vulnerable to cybercrime. It also examines their complicated tactics for entering and profiting from these sectors. This paper examines healthcare cybersecurity case studies and current research. The goal is to help readers understand the main challenges of fighting different cyberattacks. The methodology part includes a thorough literature review and rigorous analysis of data from academic sources, industry publications, and cyber security incident databases. The numbers show the diverse threat actors targeting the healthcare business, their techniques, and the vulnerabilities of healthcare institutions to cyber attacks. The report concludes that healthcare cybersecurity is crucial. The guidelines presented are essential for healthcare cybersecurity.